2013
DOI: 10.1136/bcr-2013-009410
|View full text |Cite
|
Sign up to set email alerts
|

Chryseobacterium indologenesperitonitis in peritoneal dialysis

Abstract: Peritoneal dialysis-related peritonitis remains a major complication of peritoneal dialysis in patients with end-stage renal disease. Chryseobacterium indologenes is a rare organism that has been reported to cause infections mostly in hospitalised patients with severe underlying diseases. We report the first case of C indologenes peritonitis in a patient on peritoneal dialysis outside of Asia. Our patient with end-stage renal disease on peritoneal dialysis grew C indologenes from peritoneal fluid when he prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 24 publications
0
20
0
1
Order By: Relevance
“…It is prevalent on wet or humid surfaces in hospitals and also in catheters containing fluids, such as feeding tubes, central venous catheters and tracheostomy tubes 15. The presence of contaminated medical devices in institutionalised and or immunocompromised patients, such as patients with diabetes mellitus, malignancies and neutropaenia and prolonged treatment with antibiotics, may result in serious infections 4 7 16–18. More than half of the reported cases have been among hospitalised, immunocompromised patients with mechanical ventilation or indwelling catheters 5 7 10 15.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is prevalent on wet or humid surfaces in hospitals and also in catheters containing fluids, such as feeding tubes, central venous catheters and tracheostomy tubes 15. The presence of contaminated medical devices in institutionalised and or immunocompromised patients, such as patients with diabetes mellitus, malignancies and neutropaenia and prolonged treatment with antibiotics, may result in serious infections 4 7 16–18. More than half of the reported cases have been among hospitalised, immunocompromised patients with mechanical ventilation or indwelling catheters 5 7 10 15.…”
Section: Discussionmentioning
confidence: 99%
“…The most common clinical presentations of C. indologenes infection are pneumonia, bacteraemia, cellulitis, surgical wound infections, urinary tract infections, ocular infections, meningitis due to central nervous system shunt, peritonitis due to peritoneal catheter dialysis, intra-abdominal and other catheter-related infections 4 6–8 25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Wang et al 9 reported a case of C. indologenes peritonitis in a patient with malignant ascites. In 2013, Afshar et al 10 reported a case of C. indologenes -associated peritonitis in a patient with end-stage renal disease on peritoneal dialysis. Most patients have been treated with and have responded well to piperacillin–tazobactam.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous ambulatory peritoneal dialysis (CAPD) is an important treatment option for patients with end stage renal disease [1]. Although the rate of peritonitis has declined in recent years because of improvements in CAPD, peritoneal dialysis (PD)-related peritonitis remains a major complication in patients with end-stage renal disease [2].…”
Section: Introductionmentioning
confidence: 99%